Mobile navigation system using passive infrared detector - Mohd Hasnan, Nordin (2009)
The objectives of this project is to make the maze mapper robot to move in the obstacle area. This robot are divided into three part that is microcontroller, DC motor and sensor. This robot use PIC microcontroller technology as the brain of the robot to function, DC motor for the motion or movement so that the robot can move and the infrared sensor as the detector for the robot to detect the obstacle wall which stop the robot movement and avoid it from crash those wall. It is important by knowing the background knowledge of microcontroller in order to understand a complete control system of the robot function. The schematic circuits for connection for connection of sensors and motors through PIC microcontroller are designed. Next, interfacing between PIC (microcontroller chip) and input/output hardware are drawn and integrated. Soldering process is carried out after the circuit of the electronic components on the strip board are designed. A program in PIC PBasic language source code to control the maze mapper robot is then developed. Finally, maze is constructed for the robot to move in and for the robot to map/ recognize the maze. Sensors that used for the robot are Infrared transmitters, which will be placed at the front, lea and right side of the robot. These sensors emit the infrared light, which reflected when it close to the wall. When a wall is detected, a signal sent back to the phototransistor. The microcontroller reads the signal from the sensors, and determines the appropriate DC motors. This robot will able to move in and out ofmaze automatically with minimum wall contact upon completion.